Optimalisasi Digitalisasi UMKM di Kelurahan Rungkut Kidul - Innike Fitra Farastutie; Mirda Yuma Eka Putri; Singgih Manggalou (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
At this time UMKM in the Indonesian economy play a very important role in the growth of a country. As a business person in a business that is run, an entrepreneur who runs a business must have a good marketing strategy, so that he can achieve the targets that have been planned.Today's rapidly developing technology can be utilized as a marketing medium, namely digital marketing. However, there are still many UMKM actors who do not understand and lack insight which makes UMKM actors unable to apply this media. By optimizing digital marketing, it is hoped that it will be able to develop the businesses of UMKM actors. Optimizing digital marketing is carried out in stages, first: a survey of UMKM in Rungkut Kidul. Second: conducting digital marketing outreach. Third: provide post-socialization assistance. This socialization was carried out to provide understanding and increase knowledge of digital marketing concepts. In addition, digital marketing management assistance is also carried out to improve capabilities in digital marketing management. The purpose of this service is to be able to provide solutions to marketing problems that are currently being faced by UMKM actors who are starting to enter the digital world as a product marketing process in a wider range. So that as a result of this service, UMKM actors gain knowledge about digital marketing and can expand marketing through digital marketing.